Núcleo de Educação da Infância (Childhood´s Education Center): memory and history of education in Rio Grande Do Norte (1979-2006) (Research, Society and Development, 2019)
In this article we present a bibliographical review about the history of early childhood education, since the first European institutions emerged in the first half of the 19th century, following its implantation and expansion process in Brazil during the 20th century. This work constitutes a preliminary step in a broader research that aims to investigate the representations of childhood produced in the Núcleo de Educação Infantil (Childhood´s Education Center) -NEI-CAp-UFRN, a child education institution founded in the State of Rio Grande do Norte at the end of the 1970's, here understood as space in which a living memory is woven about the education of childhood, from the date of its foundation (1979) until the year 2006, when the institution received children from 0 to 6 years of age. We believe that questions concerning the history of education, the history of childhood and its intimate relations with the collective and individual memory, will help us to understand that in the late twentieth and early twentieth century certain ways of thinking the child. childhood and education are historically constructed representations.